Lactic Dehydrogenase to Albumin Ratio Is Associated With the Risk of Stroke-Associated Pneumonia in Patients With Acute Ischemic Stroke - Yan, Dan; Huang, Qiqi; Dai, Caijun; Ren, Wenwei; Chen, Siyan (Frontiers in Nutrition, 2021)
Background: Stroke-associated pneumonia (SAP) is one of the common complications of stroke patients. Higher lactic dehydrogenase (LDH) and lower albumin levels were associated with SAP, but the contribution of the LDH to albumin ratio (LAR) to the risk of SAP in acute ischemic stroke (AIS) patients remained unclear. Methods: A total of 3173 AIS patients were included in this study, divided into SAP (n=417) and non-SAP groups (n=2756). Characteristics were compared between these two groups. The receiver operating characteristic curves (ROC) were used to evaluate the discrimination ability of the LAR, LDH, and albumin levels in predicting SAP. Logistic regression analysis was furtherly adopted to estimate the association between LAR and SAP. We also used the restricted cubic spline (RCS) to clarify the relationship between LAR and the risk of SAP. Results: LAR in the SAP group was significantly higher than that of the non-SAP group (8.75±4.58 vs 6.10±2.55, P < 0.001). According to the results of ROC, LAR had the highest prognostic accuracy compared to LDH and albumin (P<0.05). Besides, the logistic regression model showed that higher LAR (LAR>6.75) were more vulnerable to SAP (OR, 2.80; 95% CI, 2.18-3.59, P<0.001), controlling the confounders. The RCS model showed that there was a non-linear relationship between LAR and the risk of SAP. Conclusion: High LAR was associated with an increased risk of SAP in patients with AIS. LAR may be a potential predictor for the incidence of SAP. Appropriate prevention measures were needed in patients with high LAR (LAR>6.75).